Norodom Sihanouk : his mercurial art of preserving a small state - Chew, Emrys (2013)
No one has devised a universal formula for managing a small state's interests, let alone charted a foolproof course for survival. King Norodom Sihanouk's life and legacy must be appraised as a relentless game of skill to maintain Cambodia's political integrity.